2019
DOI: 10.1088/1748-9326/ab59c1
|View full text |Cite
|
Sign up to set email alerts
|

Cognition of complexity and trade-offs in a wildfire-prone social-ecological system

Abstract: Wildfire risk is a defining environmental challenge throughout much of the American West, as well as in other regions where complex social and ecological dynamics defy simple policy or management solutions. In such settings, diverse forms of land use, livelihoods, and accompanying values provide the conditions for trade-offs (e.g. between protecting homes from uncontrollable fires and restoring low-severity fire to ecosystems as a natural disturbance process). Addressing wildfire risk requires grappling with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…Taken together, our findings highlight the value of cognitive mapping for evaluating how stakeholders perceive complex sets of interactions by which prescribed fire affects valued outcomes. Cognitive mapping has been productively utilized to evaluate how stakeholders grapple with complexity in fire-prone social-ecological systems (Zaksek and Árvai, 2004;Zhang and Jetter, 2016;Walpole et al, 2017;Hamilton et al, 2019), and we advance this literature by demonstrating how the prospects of scaling up a particular management approach hinge upon perceptions of how it directly and indirectly affects a multitude of processes within the broader social-ecological system.…”
Section: The Value Of Systems Thinking In Forest and Fire Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, our findings highlight the value of cognitive mapping for evaluating how stakeholders perceive complex sets of interactions by which prescribed fire affects valued outcomes. Cognitive mapping has been productively utilized to evaluate how stakeholders grapple with complexity in fire-prone social-ecological systems (Zaksek and Árvai, 2004;Zhang and Jetter, 2016;Walpole et al, 2017;Hamilton et al, 2019), and we advance this literature by demonstrating how the prospects of scaling up a particular management approach hinge upon perceptions of how it directly and indirectly affects a multitude of processes within the broader social-ecological system.…”
Section: The Value Of Systems Thinking In Forest and Fire Managementmentioning
confidence: 99%
“…Cognitive maps ranged in size from 9 to 48 factors. Collectively, the 111 cognitive maps featured 1310 unique factors, which were assigned to parent classes (e.g., outcomes), child classes (e.g., valued outcomes), and sub-child classes (e.g., aesthetic value) as described in greater detail in Hamilton et al (2019). We analyzed cognitive maps as networks (Figures 2A,B), which allowed us to apply graph theoretic approaches to measure perception of the impact of prescribed fire on valued outcomes.…”
Section: Measurement Of Perceived Effects Of Prescribed Fire On Valuementioning
confidence: 99%
See 1 more Smart Citation
“…The frequency distribution of these micro motifs in one cognitive map -also known as directed graphlets of size two and three-can provide useful information about how one individual sees the causal interdependencies and can be used as a tool for deep-level comparisons (Tantardini et al, 2019). Theoretical and empirical studies have frequently suggested the use of 7 simple micromotifs (see Table 1) to exemplify common patterns of perceived causation (52)(53)(54)(55)(56)(57)(58). We…”
Section: Fig 1 Illustrative Samples Of Individuals With Different Lementioning
confidence: 99%
“…This is different from identifying overarching interdependencies between ambitious and high-level policy goals, or from mainly assessing how systemic factors relate to one another (the latter often assessed using cognitive mapping, e.g. Hamilton et al 2019;Özesmi & Özesmi, 2004). Hence, the question underlying this study is: how can we better assess policy issue interdependencies in ways that correspond with what measures and possible solutions policy actors have at their disposal in specific cases for specific environmental problems?…”
Section: Introductionmentioning
confidence: 99%